Educating the digital generation: the role of virtual communities - E. M. Kharlanova; N. V. Sivrikova; S. V. Roslyakova; E. G. Chernikova (Образование и наука)
Introduction. Modern educational space, as well as socialisation, exists in the framework of two interrelated components: the real (material) and virtual (digital) world. Adolescent self-realisation takes place in this mixed, or hybrid, space employing its means. One of them is virtual communities, i.e. communities existing on the platforms of digital resources, using digital devices, information and communication technologies. According to forecasts related to the near future, interaction in communities through ones digital counterparts and artificial intelligence will become a prerequisite for successful performance. However, teachers, having no experience of growing up in the conditions of the unfolding digital world, cannot always objectively assess the role of its factors and apply them as means of education.                Aim. The present research aimed to investigate the influence of virtual communities on adolescent self-realization, to determine the conditions that guarantee positive influence and, thus, to validate and justify the pedagogical guidelines that will foster constructive interaction in virtual communities.                Methodology and research methods. The study was based on the cultural-historical theory by L. S. Vygotsky. According to it, virtual communities are considered as a way of self-realization for adolescents in the context of digital society culture. Through virtual communities an adolescent undergoes socialization in a mixed environment in the course of his/her own activities and interaction with representatives of certain cultures. The constructive approach sets a course to identify the principles of teaching staff support for the subsequent teenagers’ successful usage of this tool.                Data collection was carried out in the form of an online survey using the Yandex Forms Internet service in 2022. 2996 school students of the Chelyabinsk region aged from 13 to 17 years took part in the survey. The authors employed the methods of mathematical data processing: Somers’ D-test, Kramer’s V-test, CHAID (Chi Squared Automatic Interaction Detection) analysis.                Results. The majority of teenagers (87 %) are involved in various types of virtual communities (educational, cognitive, and entertaining). The participation in virtual communities has a direct relation to involvement in different types of activities and respective satisfaction with self-realization. It generally implies being involved in several types of virtual communities, spending moderate amount of time in virtual communities, participating in virtual learning societies. Virtual communities have undeniable educational potential. The realization of this potential ensures constructive interaction and self-realization of adolescents, and requires pedagogical support.                Scientific novelty. It is proved that virtual communities influence adolescent self-realization. The article determines the conditions of the constructive virtual community influence on adolescent self-realization. The research also substantiates the pedagogical principles, which guarantee the educational potential fulfillment (polysubjectivity, productive online-offline interaction, and proactivity). Moreover, the article established that the strategy of digital educational transformation should set a course to the transition from ensuring accessibility and security in a virtual environment to managing virtual communities for the purpose of the self-development and self-realization.                Practical significance. The research outcomes may be applied for the development of educational programmes and the implementation of educational activity in the realities of a digital world.